Agathokles of Syracuse: Sicilian tyrant and Hellenistic king - de Lisle, C (2017)
This thesis discusses Agathokles of Syracuse (r. 317-289), arguing that he should be understood in both the context of local Greek Sicilian traditions and contemporary Hellenistic developments, whereas previous studies have represented him as remaining apart from the Hellenistic world as a Sicilian dead end or embracing the Hellenistic world so enthusiastically that he abandoned his Sicilian context altogether. Thus this is a thesis about chronological continuity at the beginning of the Hellenistic period and geographical continuity between Sicily and the wider Mediterranean region. The thesis is tripartite. The first part deals with literary and numismatic source material, arguing for a shift away from source criticism in order to emphasise the coherence and agency of the surviving literary texts and the relationship of characterisations of Agathokles to broader Greek representations of autocracy. I discuss the chronology, iconography, and circulation of Agathokles' coinage, as evidence for the combination of Sicilian and Hellenistic elements. The second part discusses Agathokles' rulership style, arguing that the assumption of the royal title did not transform his rule and identifying substantial parallels with his predecessors and his contemporaries. This suggests that Sicilian tyranny and Hellenistic monarchy were aspects of a single Greek tradition of autocracy. The third part of the thesis looks at Agathokles' interactions with Sicily, Carthage, Italy, Mainland Greece and the Diadochoi, identifying the dynamics which drove these interactions and showing how they continued older models of interaction and were shaped by contemporary developments. This demonstrates the degree to which Agathokles and his local Sicilian context were part of the wider Hellenistic world.